Social support in senior groups of the department of Quindio (Revista de Investigaciones Universidad del Quindío, 2013)
The article is made of the results presented in 2006, with the implementation of the research project report “Organization, leadership and participation in groups seniors of the Department of Quindío”, responding to one of the objectives of the research: describe the types of support available to seniors organizations Quindío department. This 196 surveys were applied to seniors organizations, through a simple proportional random sampling, with a margin of error of 7% and 95% confidence. In relation to the types of support, the results indicate that organizations supported mainly municipal and departmental administrations (67.9%) with the implementation of the food programme for the Mayor “Juan Luis Londoño de la Cuesta” adult and the direct subsidy programme for social protection of the adult Mayor “PPSAM”.
Keywords: support; ageing; seniors; system of social protection and ageing